Safety assessment of fragile environment in Badain Jaran Desert and its surrounding areas based on the DPSIR model - Haiyang Xi; Yuqing Chen; Xinyue Zhao; Celestin Sindikubwabo; Wenju Cheng (Ecological Indicators, 2023)
An objective and comprehensive understanding of the safety conditions of the ecological environment is of great significance for regional social economic development and ecological environmental protection. Based on the Driving force-Pressure-State-Impact-Response (DPSIR) model, 40 indicators were selected to construct an ecological environment safety assessment system, and to evaluate ecological environment safety status for the Badain Jaran Desert and its surrounding areas (BJDCA) from 2001 to 2019. The results show that 1) From 2001 to 2019, the ecological and environmental security situation in the BJDCA showed a benign development trend. After 2010, the safety level reached the basic safety level as a medium stage out of five safety level stages. 2) The improvement of ecological and environmental security level resulted from the joint actions of socio-economic development and ecological restoration measures. In the future, the BJDCA may continue to face a series of ecological and environmental pressures brought by socio-economic developments. Therefore, we recommend an active adjustment of the development mode and proportion of the three major industries, adhering to the direction of sustainable development and ensuring the benign development of socio-economic conditions and the ecological environment. This study can provide data to support for regional ecological environment restitution and policy formulation.